Muhammad Iqbal’s Islamic Philosophy Concept of Education Contextualised in Facing the Disruptive Era - Badrul Munir Chair (USIM Press, 2024)
Vol. 24 No. 1 (2021): Journal of Islamic Social Sciences and Humanities